2009
DOI: 10.1289/ehp.0900765
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Cadmium Exposure, Neurodevelopment, and Blood Pressure in Children at 2, 5, and 7 Years of Age

Abstract: BackgroundAdverse health effects of cadmium in adults are well documented, but little is known about the neuropsychological effects of cadmium in children, and no studies of cadmium and blood pressure in children have been conducted.ObjectiveWe examined the potential effects of low-level cadmium exposure on intelligence quotient, neuropsychological functions, behavior, and blood pressure among children, using blood cadmium as a measure of exposure.MethodsWe used the data from a multicenter randomized clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
4
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 40 publications
1
53
4
2
Order By: Relevance
“…These findings suggest that blood may not be an optimal compartment for biomonitoring of these metals, at least in young children. In contrast, Cd was detected in approximately half the blood samples of children identified with high blood lead concentrations in a study in the United States (Cao et al, 2009), and was detected in the majority of German fourth-graders (Link et al, 2007), with average concentrations in both studies considerably higher than those in this study.…”
Section: Discussioncontrasting
confidence: 91%
“…These findings suggest that blood may not be an optimal compartment for biomonitoring of these metals, at least in young children. In contrast, Cd was detected in approximately half the blood samples of children identified with high blood lead concentrations in a study in the United States (Cao et al, 2009), and was detected in the majority of German fourth-graders (Link et al, 2007), with average concentrations in both studies considerably higher than those in this study.…”
Section: Discussioncontrasting
confidence: 91%
“…Moreover, cadmium concentration in urine (that may be used as a biomarker of exposure in early pregnancy), even at low doses, was associated to decreased IQ scores in children (Kippler et al 2012a). Cao et al (2009) did not observe any significant relationship between blood cadmium levels, as a result of postnatal exposure, and neurodevelopmental scores in children at 2, 5, and 7 years of age. Children 6-15 years of age who had higher urinary Cd concentrations showed an increased risk of learning disabilities; in contrast, the association with ADHD did not reach statistical significance (Ciesielski et al 2012) as previously observed through evaluation of Cd concentration in blood of school-aged children with ADHD (Yousef et al 2011).…”
Section: Neurotoxic Effectscontrasting
confidence: 60%
“…High concentrations of Cd in the soil and water supply mean that it is readily detectable in meat, fish, vegetables, and fruits (Ishitobi et al 2007). In addition to diet (primarily cereals and vegetables), which represents the main source of cadmium intake in the non-smoking general population, exposure to Cd may also occur through environmental tobacco smoke, house dust, and active smoking (Järup et al 1998;Cao et al 2009). Once it entered the body, Cd accumulates in the liver and kidney, and the highest concentrations may be observed in the renal cortex (U.S. Environmental Protection Agency 1997; Cao et al 2009).…”
Section: Cadmiummentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of children with blood lead levels greater than 10 mg/dL was 88.0%, with 10.2% (147/167) having blood lead levels higher than 20.0 mg/dL. In addition, the blood cadmium levels observed in this study exceeded the current range of normal values (#0.2 mg/L) [34,35]. However, no different of blood lead and cadmium were found between male and female.…”
Section: Pbde Levels In Childrencontrasting
confidence: 57%